2017
DOI: 10.1111/imj.13252
|View full text |Cite
|
Sign up to set email alerts
|

Impact of providing patients with copies of their medical correspondence: a randomised controlled study

Abstract: Patients wish to receive copies of their correspondence and feel it improves their understanding of their medical condition. Although we were unable to demonstrate a measurable reduction in anxiety, increase in understanding or satisfaction, we recommend that patients be offered the choice of receiving copies of their clinic correspondence and endoscopy reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…The study participants, in line with past studies [15][16][17][18][19][20][21][22][23][24]65], showed high rates of preference for receiving letters. Sending patients direct copies of GP letters was not only favoured by many of the patients but could save time and resources through eradicating the need to produce two separate discharge letters (i.e.…”
Section: Implications For Practicesupporting
confidence: 85%
See 2 more Smart Citations
“…The study participants, in line with past studies [15][16][17][18][19][20][21][22][23][24]65], showed high rates of preference for receiving letters. Sending patients direct copies of GP letters was not only favoured by many of the patients but could save time and resources through eradicating the need to produce two separate discharge letters (i.e.…”
Section: Implications For Practicesupporting
confidence: 85%
“…Generally, participants' opinions about receiving copies of letters were viewed as a matter of personal preference rather than specific to particular specialties or episodes of care. Participants felt patients should be offered a choice about when and whether they wish to receive a copy letter, a view supported by findings from past studies [8,16,19,60]. Responses seemed to exhibit preference for "opt-out" letter receipt systems which would account for individuals who do not want letters whilst still allowing the majority of patients to receive letters.…”
Section: Key Findingsmentioning
confidence: 74%
See 1 more Smart Citation
“…Past studies, across a range of settings, report that patient preference for receiving letters is high (79%-97%) [39][40][41][42][43][44][45][46] ; this study supports this finding as patients generally indicated preference for discharge letter receipt. Despite this, both GPs and patients noted the inconsistent practice of patients receiving letters.…”
Section: Patient Preference/choicesupporting
confidence: 80%
“…The initiative encourages doctors to write directly to patients in simple plain English to increase understanding. Despite these initiatives and guidelines, evidence within and outside the UK reports both benefits6–10 (eg, patient satisfaction), and drawbacks11–15 (eg, patient confusion) of patients receiving their letters. While patients receive copies of discharge letters inconsistently,16 17 the reasons for this and the subsequent consequences remain unclear.…”
Section: Introductionmentioning
confidence: 99%